King, priest, prophet : positive eschatological protagonists of the Qumran library - Xeravits, Géza G. (Studies on the Texts of the Desert of Judah, 2003)
Among the newly published texts of the Qumran Library there are a good number with eschatological content. Some of these texts relate the eschatological activity of certain figures who seem to play an important role in the events of the eschaton. This study explores these figures. The material of this study is divided into two main parts. The first is analytical, in which the related textual material is investigated, each passage in turn. The second, systematic section contains the evaluation and discussion of the data provided by the analyses of the first part. These analyses are especially relevant for scholars of both the Old and New Testaments and for all those interested in early Jewish thought at the turn of the era.